Pengaruh Kombinasi Pupuk NPK Majemuk dan Fermentasi Air Cucian Beras Terhadap Pertumbuhan Tanaman Selada Keriting (Lactuca sativa L.) Varietas Grand Rapids - Indira Oktaviani Shabila; Hayatul Rahmi; Tatang Surjana (Jurnal Ilmiah Wahana Pendidikan, 2021)
The experiment was carried out in an experimental garden located in Gg. Lebaksari, Wadas, Telukjambe Timur District, Karawang, West Java from March to June 2021. The research method used was an experimental method with a single factor Randomized Block Design (RBD) with 7 treatment combinations and repeated 4 times, the treatments consisted of: A(Without Treatment), B (300 kg/ha NPK), C (200 ml/litre rice washing water), D (250 kg/ha NPK + 100 ml/lt rice washing water), E (250 kg/ha NPK + 50 ml/lt rice washing water), F (200 kg/ha NPK + 100 ml/lt rice washing water), G (200 kg/ha NPK + 50 ml/lt rice washing water). The results of this study showed that the combination of compound NPK fertilizer and fermented rice washing water had a significant effect on plant heights at 14 and 28 days and on the number of leaves 7 and 28 days after planting. Treatment D was a combination of NPK 250 kg/ha + fermented rice washing water 100 ml/lt gave the best results for plant height 14 hst and treatment G was a combination of NPK 200 kg/ha + fermented rice washing water 50 ml/lt gave the best results for the amount of leaves 7 hst.